Using Administrative Data to Evaluate the Effectiveness of Home Visiting Programs for Improving the Well-Being of First Nations Children and Parents - Chartier, Mariette; Brownell, Marni; Nickel, Nathan; Campbell, Rhonda; Phillips-Beck, Wanda; Enns, Jennifer; Sarkar, Joykrishna; Burland, Elaine; Chateau, Dan (International Journal of Population Data Science, 2018)
Introduction The province-wide Families First Home Visiting Program (FFHV) provides home visiting to families with children living in conditions of risk. It remains unknown if First Nations families are benefiting from the program. Using existing administrative and population-wide data is an innovative practice to evaluate programs that have been scaled up. Objectives and Approach The objective is to determine FFHV’s effectiveness at improving outcomes for First Nations children and parents. The partnership with First Nations Health and Social Secretariat of Manitoba facilitated access to First Nations identifiers and provided guidance in conducting the study. Program data from 4,010 First Nations children and parents were linked at an individual-level to administrative data housed at the Manitoba Centre for Health Policy. We compared the predictive probability of outcomes of program and non-program families. Inverse probability of treatment weights were used to adjust for confounders related to both entry into FFHV and the outcomes under study. Results The cohort of First Nations children and parents was successfully linked through an individual scrambled health identifier. FFHV was associated with higher rates of child immunization at age one (71% versus 66%) and age two (47% versus 41%) and parental involvement in community support groups (21% versus 17%). It was also associated with lower rates of being in care of child welfare at age one (10% versus 14%) and age two (15% versus 19%); maltreatment-related hospitalizations at age three (0.4% versus 1.0%); and child victimization as measured by justice system records (1.7% versus 3.0%). However, there were no differences in being “not ready for school” between the two groups of children, nor between the groups of mothers in physician visits for mental health reasons. Conclusion/Implications Home visiting services can play a role in supporting healthy development of First Nations children by providing support to parents and connecting children to health and social services, however, there also remains an urgent need for long term strategies to address structural inequality and the ongoing effects of colonization.